Analisa Metode SHA224 Untuk Mendeteksi Orisinalitas Citra Digital - Rusman Halawa (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
In a digital image it is very important that the name of the authenticity of the data, given the data contained in it is very important and very confidential from parties who are not obliged to want to damage and change the information contained therein so it does not match what is expected. So, it is necessary to apply data security that can protect the data so that it cannot be manipulated or damaged any information contained in the data. Cryptography is the study of mathematical techniques related to aspects of information security such as data confidentiality, data integrity of data integrity, and data authentication. But not all aspects of information security can be solved by cryptography. Cryptography can also be interpreted as a science or an art to maintain message security. Some of the problems above that need to be considered and understood so that the system applied in accordance with what is desired by all parties. In digital images, the main thing that must be observed is to maintain the authenticity of digital images and improve the quality problems of digital images that you want to manipulate. With this research can overcome all the problems that occur about manipulating data from parties who are not obliged to the data From the above research the purpose of SHA224 is to secure a form of digital images that are still original that want to be manipulated by other parties. The image can be seen or manipulated anyone who has rights or obligations in the data or has no obligation at all, but when securing data using the SHA224 method, the data resulting from manipulation and original data will be detected and the results will be seen in fact. With the SHA224 method it can maintain the security and authenticity of digital images. In testing this can be done with the SHA224 method using the MATLAB application.